Assessing favipiravir impact on SARS-CoV-2 transmission within households: Insights from a multi-center study (FaviPrev) - Taweegrit Siripongboonsitti; Marisa Muadchimkaew; Kriangkrai Tawinprai; Ornisa Issaranon; Wichuda Meepholkij; Pureepat Arttawejkul; Apiradee Vararungzarit; Onwalee Dhissayakamol; Wilaiporn Preeyachit; Kamonwan Soonklang; Nithi Mahanonda (Journal of Virus Eradication)
Background: While certain studies have demonstrated that antiviral treatment administered to index patients with influenza can mitigate the transmission within households, the efficacy of anti-SARS-CoV-2 agents in curtailing household transmission remains to be conclusively established. Methods: A retrospective study conducted from April 2021 to May 2022 across multiple centers in Thailand compared 892 individuals treated with favipiravir to 84 who received standard treatment among mild to moderate COVID-19 index patients. The study focused on the impact of favipiravir treatment in reducing household SARS-CoV-2 transmission by examining the secondary attack rate. Results: Favipiravir significantly reduced household SARS-CoV-2 transmission, comparing 1836 household contacts with favipiravir-treated index cases to 170 contacts whose index cases received standard care. Favipiravir led to a 58 % secondary attack rate, substantially lower than the 71.8 % observed with standard treatment, representing a 54 % reduction in transmission likelihood, with an odds ratio of 0.46 (95 % confidence interval [CI] [0.23–0.89]). Index cases treated with favipiravir also demonstrated a relative risk reduction of 0.19 in transmission (95 % CI [0.11–0.27]). Remarkably, favipiravir effectiveness was most notable in unvaccinated index cases, those with symptomatic infections, individuals living in shared spaces like dormitories, flats, or apartments, and those not adhering to mask-wearing within their households. Conclusions: Favipiravir has demonstrated in this study an indirect role in reducing household SARS-CoV-2 transmission, showing notable efficacy in symptomatic and unvaccinated index cases. This breakthrough highlights its potential in broader public health strategies. Exploring the roles and challenges of other anti-SARS-CoV-2 agents remains a vital goal in ongoing research.